Collaborating profitably? The fundraising practices of the contemporary art society, 1919–1939. Issue 1 (2nd January 2023) - Herrero, Marta; Buckley, Thomas R.
Abstract: This article provides a new understanding of how organisations from the profit and non-profit sectors collaborated to fundraise for the arts in Interwar Britain. The central focus is the Contemporary Art Society (CAS) an organisation established in the belief that the art being acquired for national collections was inadequate. Based on an analysis of CAS committee members; the relationship between the CAS and commercial galleries through the Society's subscriber scheme; and a number of collaborative exhibitions organised between 1919 and 1939, we argue that the CAS exercised cultural entrepreneurship, raising revenue to shape a new direction for the British Artworld.